Interaction of the human T-cell lymphotropic virus type 1 tax transactivator with transcription factor IIA. - Clemens, K E (1996)
The Tax protein of human T-cell lymphotropic virus type 1 (HTLV-1) is a 40-kDa transcriptional activator which is critical for HTLV-1 gene regulation and virus-induced cellular transformation. Tax is localized to the DNA through its interaction with the site-specific activators cyclic AMP-responsive element-binding protein, NF-kappaB, and serum response factor. It has been suggested that the recruitment of Tax to the DNA positions Tax for interaction with the basal transcriptional machinery. On the basis of several independent assays, we now report a physical and functional interaction between Tax and the transcription factor, TFIIA. First, Tax was found to interact with the 35-kDa (alpha) subunit of TFIIA in the yeast two-hybrid interaction system. Importantly, two previously characterized mutants with point mutations in Tax, M32 (Y196A, K197S) and M41 (H287A, P288S), which were shown to be defective in Tax-activated transcription were unable to interact with TFIIA in this assay. Second, a glutathione-S-transferase (GST) affinity-binding assay showed that the interaction of holo-TFIIA with GST-Tax was 20-fold higher than that observed with either the GST-Tax M32 activation mutant or the GST control. Third, a coimmunoprecipitation assay showed that in HTLV-1-infected human T lymphocytes, Tax and TFIIA were associated. Finally, TFIIA facilitates Tax transactivation in vitro and in vivo. In vitro transcription studies showed reduced levels of Tax-activated transcription in cell extracts depleted of TFIIA. In addition, transfection of human T lymphocytes with TFIIA expression vectors enhanced Tax-activated transcription of an HTLV-1 long terminal repeat-chloramphenicol acetyltransferase reporter construct. Our study suggests that the interaction of Tax with the transcription factor TFIIA may play a role in Tax-mediated transcriptional activation.